The Mopra Southern Galactic Plane CO Survey — Data Release 1. (20th May 2015) - Braiding, Catherine; Burton, M. G.; Blackwell, R.; Glück, C.; Hawkes, J.; Kulesa, C.; Maxted, N.; Rebolledo, D.; Rowell, G.; Stark, A.; Tothill, N.; Urquhart, J. S.; et al.
Abstract: We present observations of the first 10° of longitude in the Mopra CO survey of the southern Galactic plane, covering Galactic longitude l = 320–330° and latitude b = ±0.5°, and l = 327–330°, b = +0.5–1.0°. These data have been taken at 35-arcsec spatial resolution and 0.1 km s −1 spectral resolution, providing an unprecedented view of the molecular clouds and gas of the southern Galactic plane in the 109–115 GHz J = 1–0 transitions of 12 CO, 13 CO, C 18 O, and C 17 O. Together with information about the noise statistics from the Mopra telescope, these data can be retrieved from the Mopra CO website and the CSIRO-ATNF data archive.